МЕТОДИКА ОЦЕНКИ ГИПОТЕЗЫ ЭФФЕКТИВНОГО РЫНКА (ГЭР) В РАЗВИВАЮЩИХСЯ СТРАНАХ (Journal of Economic Research & Business Administration, 2015)
This paper investigates efficient market hypothesis. Moreover, paper considers factors such as thin trading, nonlinearity, institutional evolution which negatively impact for emerging markets to be efficient. Further paper shows Methodology proposed by Antoniou et al 1997 that tests EMH in emerging markets taking in account unique to the stock markets of emerging economies.